Hypothetical Evaluations of Positive and Negative Alcohol Consequences in Adolescents across Various Levels of Drinking Experience - Merrill, Jennifer E. (Psychol Addict Behav, 2016)
Research supports the importance of the subjective evaluation of alcohol-related consequences, and theory suggests that these evaluations may depend on one’s prior experience. The goal of the present study was to understand how adolescents subjectively evaluate the potential negative and positive consequences of drinking and to test the hypothesis that evaluations differ as a function of personal experience with alcohol use and consequences. Participants were 697 adolescents (55% female) who completed online surveys assessing lifetime drinking experience and hypothetical evaluations of 13 negative and 9 positive consequences. Never having consumed a full drink of alcohol (vs having consumed a full drink, but not having negative consequences) was significantly associated with higher mean negative evaluations and lower mean positive evaluations. Those who had a full drink (vs. those who had not) rated close to half of the negative consequence items as significantly less bothersome, and all of the positive consequences as significantly more enjoyable. However, there was little evidence in this sample that evaluations differ between drinkers with and without experience with negative consequences. Overall, findings suggest that youth who have experience with simply consuming alcohol may place more value on the positive and less value on some of the negative consequences of drinking, which has the potential to impact decisions to continue to drink. Longitudinal research uncovering the direction of evaluation-experience effects and mechanisms other than consequence experience, are essential next steps.